Antioxidant and Anti-Inflammatory Effects of Traditional Medicinal Plants for Urolithiasis: A Scoping Review - Brenda Pacheco-Hernández; Teresa Ayora-Talavera; Julia Cano-Sosa; Lilia G. Noriega; Neith Aracely Pacheco-López; Juan M. Vargas-Morales; Isabel Medina-Vera; Martha Guevara-Cruz; Rodolfo Chim-Aké; Ana Ligia Gutiérrez-Solis; Roberto Lugo; Azalia Avila-Nava (Plants)
Urolithiasis (UL) is the presence of stones in the kidneys or urinary tract; its prevalence has increased worldwide. Thus, strategies have been sought to reduce it and one of them is the use of medicinal plants due to their accessibility, low cost, and cultural traditions. Studies on traditional medicinal plants in UL mainly documented results of litholytic and urinary parameters. Although, stone formation is related to oxidative stress and inflammation, and only a few studies are focused on these types of biomarkers. Thus, the aim of the present review was to summarize studies showing the antioxidant and anti-inflammatory effects of traditional medicinal plants used in UL management. We performed a scoping review; the database sources used were MEDLINE/PubMed, Google Scholar, SpringerLink, Scielo and Redalyc. From a total of 184 studies screened, six were included from China (2), India (3), and Corea (1). These studies have shown the antioxidant and anti-inflammatory effects of traditional medicinal plants, including Glechoma longituba (G. longituba), Bergenia ligulate (B. ligulate), Lygodium japonicum (L. japonicum), Citrus limon (C. limon), Xanthium strumarium (X. strumarium) and Tribulus terrestris (T. terrestris). They have also described their molecular mechanism of antioxidant and anti-inflammatory effects through the activation of antioxidant genes induced by Nrf2 or by suppressing the inflammatory gene expression by the inhibition of NFκ-B. These effects could be modulated by their bioactive compounds, such as polyphenols, flavonoids, tannins, saponins, and terpenes, present in these plants. This review summarizes the antioxidant and anti-inflammatory effects of traditional medicinal plants and highlights their molecular mechanisms of action and main bioactive compounds. This evidence may be used in biotechnology and synthetic biology areas for the development of new products from plant-derived compounds to reduce the high recurrence rates of UL.